Entre Sociais, Roles E Bailes: Uma Etnografia Dos Entretenimentos Juvenis No Capão Redondo - Pinto, Felipe De Souza [UNIFESP] (2018)
This is a survey about the youth entertainment at Capão Redondo, a suburb district in the south São Paulo, state capital. My starting point was my experience as sociology teacher for High School, I was looking for different types of leisure, the social, rolê, party and the baile. Through the knowledge and the way, they act, their economy administration, history, environment, imagination schemes of fun and their network of relationship, I move an interpretation considering the number of people linked, the degree of their relations, the place which they are carried out, the time of organization of the same, its structures and, finally, what they are ordinary or extraordinary.